The effect and mechanism of farmland transfer on the multidimensional relative poverty of rural women - Li, Mengding; Zheng, ZhiJia; Zheng, Jiaxi; Yang, Dong; Wang, Tingyu (Frontiers in Environmental Science, 2023)
Introduction: Over the past 40 years of reform and opening up, China has made significant progress in poverty reduction in rural areas. China’s land system is different from that of other countries in the world because of its special national conditions and the influence of small farmers in large countries. The rural female labor force is the key force to reduce rural poverty and realize rural revitalization. Methods: This paper attempts to construct a multidimensional relative poverty measurement index system for rural women and estimates the multidimensional relative poverty of the rural female labor force using the data of China Family Panel Studies in 2018. This paper also uses propensity score matching to estimate the correlation between rural land transfer and rural female poverty. Results and discussion: Based on the aforementioned conclusions, this paper puts forward relevant policy suggestions from two aspects: encouraging the rational and effective transfer of agricultural land and breaking the inherent gender order 1) to encourage the rational and effective circulation of agricultural land, so as to reduce the degree of fragmentation and promote the appropriate scale management of contiguous plots; 2) to break the inherent gender order, so as to achieve the improvement of women’s economic income, and the alleviation of multidimensional relative poverty, so as to alleviate the poverty of families.